2021
DOI: 10.3390/jof7090772
|View full text |Cite
|
Sign up to set email alerts
|

Mercury in Macrolepiota procera (Scop.) Singer and Its Underlying Substrate—Environmental and Health Risks Assessment

Abstract: Wild-growing edible mushrooms are valuable food with a high content of proteins, fibers, antioxidants, and they are characterized by their specific taste and flavor. However, from an ecotoxicological point of view, they are a risk commodity because of their extremely high bioaccumulative capacity to accumulate the risk elements and contaminants from the environment. In the present study, we examined mercury (Hg) contamination in 230 fruiting bodies of Macrolepiota procera (Scop.) Singer and 230 soil/substrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The average Hg content detected in Leccinum scabrum was 1.41 (0.674–2.94) mg kg −1 DW. Jančo et al [ 41 , 49 ] also confirmed the significant effect of the locality on the total Hg content in edible parts of mushrooms. Some previous studies showed that Macrolepiota procera collected from Central Slovakia (Banská Bystrica) had an average Hg concentration of 1.98 mg kg −1 (from 0.41 to 3.20 mg kg −1 ) in the caps and 1.40 mg kg −1 (from 0.12 to 1.75 mg kg −1 ) in stems.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…The average Hg content detected in Leccinum scabrum was 1.41 (0.674–2.94) mg kg −1 DW. Jančo et al [ 41 , 49 ] also confirmed the significant effect of the locality on the total Hg content in edible parts of mushrooms. Some previous studies showed that Macrolepiota procera collected from Central Slovakia (Banská Bystrica) had an average Hg concentration of 1.98 mg kg −1 (from 0.41 to 3.20 mg kg −1 ) in the caps and 1.40 mg kg −1 (from 0.12 to 1.75 mg kg −1 ) in stems.…”
Section: Resultsmentioning
confidence: 86%
“…al. [ 41 ], specifically in the locality Snina (0.68 mg kg −1 ). Lower values of Hg content in soil/substrate from Central Slovakia were recorded by Árvay et al [ 42 ] where the content of total Hg in the soil/substrate varied between 0.05 and 0.27 mg kg −1 DW.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations